A Theological Evaluation of the Utopian Image of Prosperity Gospel and the African Dilemma - Ehioghae, Efe M.; Olanrewaju, Joseph A. (IOSR Journal of Humanitites and Social Science, 2015)
Prosperity gospel may be traced to the emergence of modern Pentecostalism which bestrides the world like a colossus; and Africa is one major continent where its influence is pervasive. Pentecostalism’s emphasis on material prosperity may account for this. Many countries in Africa struggle under the huge burden of poverty which has made them susceptible to any ideology that could change the unsavory situation. Prosperity gospel promises to bridge the yawning chasm between the rich and the poor, thus creating a semblance of utopian community where all are beneficiaries of the material comforts of life through faith. Both the theology and hermeneutics of prosperity gospel are implicated as a faulty premise for a belief in material prosperity. Bible passages such as Mark 10:29,30 and 3 John 2, often cited to bolster prosperity gospel, bristle with difficulties. The interpretations of such passages are skewed to support material prosperity. In essence, while prosperity gospel feeds the greed of its peddlers it emasculates the spirituality of believers. The utopian image presented by prosperity gospel is a mirage; many believers are worse off materially because of a faith that lacks sound biblical basis.
free